On the species and related problems - Yatracos, Yannis G. (My University, 1991)
Starr (1979) has proved that in the species problem, Robbins' estimate in a search of size n + m has negative correlation with the quantity of interest Un, m ≥ 1; Un, the probability of the unobserved species in a search of size n is a random function of a parameter. Nevertheless the question whether or not one could do better was left open. An estimate Vn,m is provided that has high positive correlation with Un. The form of the proposed estimate Vn,m suggests a natural class of estimates that are highly (positively) correlated with the random function of the parameter that is of interest at any given situation when additional sampling is allowed. Finally, a class of functions of the probabilities of the unobserved species, that cannot be estimated in an unbiased way without additional searches is also offered.
Keywords: Species; Parameter estimation; Functional analysis